Borobudur tourist destination recommendation system using Case Base Reasoning (CBR) method - Nurul Hanifatul Alfiyah; Andi Widiyanto; Agus Setiawan (Borobudur Informatics Review, 2021)
The high interest of tourists to Borobudur Temple does not have the same impact on tourist destinations around Borobudur Temple. Tourists have difficulty with several tourist destinations around Borobudur Temple that are in accordance with tourist interests. Tourists need proposed tourist destinations that match the desired criteria. In this study the Case Base Reasoning (CBR) method was used to create a tourist destination recommendation system with variables such as distance, type, location, and tourist attraction. The results of testing the tourist destination recommendation system showed that respondents felt it was helped 86.67%, 88.33% as desired and 85.41% said they were satisfied